Building Customer Loyalty in the Digital Economy Era: The Role of CRM Innovation and Promotional Strategies at Smarco Superstore Ring Road City Walks Medan: Membangun Loyalitas Pelanggan di Era Ekonomi Digital: Peran Inovasi CRM dan Strategi Promosi di Smarco Superstore Ring Road City Walks Medan - Bernadetha Manurung; Hommy Dorthy Ellyany Sinaga (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
This study examines the impact of Customer Relationship Management (CRM) and sales promotion on customer loyalty at Smarco Superstore Ring Road City Walks Medan. The research is grounded in the challenges of modern retail competition with the rise of e-commerce and the shift in consumer behavior toward digitalization, which highlight the need for effective CRM and promotional strategies. A quantitative survey method was applied, using primary data collected from 96 purposively selected respondents through a Likert-scale questionnaire. Data were analyzed using multiple linear regression, along with validity and reliability tests, classical assumption testing, t-test, F-test, and coefficient of determination. Results show that CRM has a positive but insignificant partial effect on loyalty, while sales promotion has a positive and significant partial effect. Together, CRM and sales promotion significantly influence loyalty with a contribution of 40.7%, leaving the remainder to other factors. The findings highlight the importance of consistent sales promotion and optimized CRM to enhance sustainable customer loyalty.